Purification, crystallization and preliminary X-ray diffraction analysis of a class P-III metalloproteinase (BmMP-III) from the venom of Bothrops moojeni - Ullah, Anwar [UNESP]; Campos Brasil de Souza, Tatiana de Arruda; Masood, Rehana [UNESP]; Murakami, Mario Tyago; Arni, Raghuvir Krishnaswamy [UNESP] (Wiley-Blackwell, 2012)
Snake-venom metalloproteinases (SVMPs) comprise a family of haemostatically active toxins which can cause haemorrhage, coagulopathy, inhibition of platelet aggregation and inflammatory response. These effects are attributed to the proteolytic action of SVMPs on extracellular matrix components, plasma proteins and cell-surface proteins. SVMPs are classified into four classes (P-I to P-IV) based on their domain structures. In order to understand the multiple roles played by the domains of P-III SVMPs, a P-III SVMP (BmMP-III) from the venom of Bothrops moojeni was purified, characterized and crystallized. The crystals belonged to space group I4(1)22, with unit-cell parameters a = b = 108.16, c = 196.09 angstrom. Initially, flash-cooled crystals diffracted poorly to a resolution of about 10 angstrom. However, a significant improvement in the diffraction resolution was observed upon annealing and a complete data set was collected to 3.3 angstrom resolution. The asymmetric unit contained one molecule and the structure was determined and partially refined to an R factor of 34%. Structural comparisons indicated that the cysteine-rich domain can adopt different conformations in relation to the catalytic domain, which may modulate the enzyme activity.